2020
DOI: 10.1002/adma.202003746
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Anomalous Charge Density Wave States in Graphene/NbSe2 Heterostructures

Abstract: Metallic layered transition metal dichalcogenides (TMDs) host collective many‐body interactions, including the competing superconducting and charge density wave (CDW) states. Graphene is widely employed as a heteroepitaxial substrate for the growth of TMD layers and as an ohmic contact, where the graphene/TMD heterostructure is naturally formed. The presence of graphene can unpredictably influence the CDW order in 2D CDW conductors. This work reports the CDW transitions of 2H‐NbSe2 layers in graphene/NbSe2 het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 49 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Chen et al reported temperature-dependent Raman spectroscopy of alloy Mo 1– x W x S 2 monolayers with five different component x values and found the FOT coefficients of all appearing modes changed regularly with the W component increases, which may originate from composition disorder, phonon anharmonicity, and thermal expansion . It is worth mentioning that temperature-dependent Raman spectroscopy of vdW crystals is not only applied to study thermal properties like phonon anharmonicity but also used to study many interesting issues, such as charge density waves and magnetic phase transitions, which show phonon shifts different from the traditional one discussed above and are beyond the scope of this work. Temperature-dependent phonon shift is indeed affected by many internal and external mechanisms, and to explore one certain factor, the measurement of temperature-dependent Raman spectroscopy should strictly control the variables.…”
Section: Basic Theoretical Modelmentioning
confidence: 99%
“…Chen et al reported temperature-dependent Raman spectroscopy of alloy Mo 1– x W x S 2 monolayers with five different component x values and found the FOT coefficients of all appearing modes changed regularly with the W component increases, which may originate from composition disorder, phonon anharmonicity, and thermal expansion . It is worth mentioning that temperature-dependent Raman spectroscopy of vdW crystals is not only applied to study thermal properties like phonon anharmonicity but also used to study many interesting issues, such as charge density waves and magnetic phase transitions, which show phonon shifts different from the traditional one discussed above and are beyond the scope of this work. Temperature-dependent phonon shift is indeed affected by many internal and external mechanisms, and to explore one certain factor, the measurement of temperature-dependent Raman spectroscopy should strictly control the variables.…”
Section: Basic Theoretical Modelmentioning
confidence: 99%
“…The layered transition metal dichalcogenides (TMDs), NbX 2 (X= S, Se), are intensively studied as typical platforms for revealing the microscopic mechanism of CDW phases. The Fermi surface nesting and saddle-point singularities are usually proposed as driving mechanisms of CDW transition in previous studies. More recently, the momentum-dependent electron–phonon coupling (EPC) is recognized as an important factor. Though progress has been made, it is still now a mystery why the isoelectronic and isostructural compounds NbS 2 and NbSe 2 show distinct CDW features in experiments. In contrast to a bulk (2 H ) NbSe 2 with the CDW transition temperature ( T CDW ) of ∼33 K, the 2 H -NbS 2 displays no CDW instability. , At the two-dimensional (2D) limit, the reported T CDW of single-layer (1 H ) NbSe 2 ranges from 45 to 140 K from different experimental groups; while the appearance of CDW order in the 1 H -NbS 2 systems depends strongly on the underlying substrates. ,, Although some different CDW features in NbS 2 and NbSe 2 are partially explained by the competition of charge transfer, EPC, and electron correlation, a systematic analysis is needed to estimate contributions from these factors including the nuclear quantum effects (NQEs).…”
mentioning
confidence: 99%
“…The covalent bonds in the non-layered structure may replace the role of pressure or substrate strain in the layered materials. 20,42,43 Although the abrupt change in the resistance was not very drastic, this is the first report of the room-temperature CDW phase transition in non-layered materials.…”
Section: Resultsmentioning
confidence: 80%